1993
DOI: 10.1002/masy.19930660118
|View full text |Cite
|
Sign up to set email alerts
|

Ti complex catalysts including thiobisphenoxy group as a ligand for olefin polymerization

Abstract: Absaact: Titanium complexes were prepared by the reaction of 2,2'-thiobis(6-mbutyl-4-methylphenol) (TBP) with TiC1, or Ti(OPf),.These complexes in combination with methyalumoxane as cocatalyst are highly active towards ethylene and propene, giving polymers having high molecular weights. The polymerization activities for ethylene-and propene are comparable to those of Cp2ZrC MA0 catalyst. Polypropylene obtained had extremely high molecular weigk (Mw>6 million) and low regioregularity (30% of head-to-head and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 14 publications
3
45
3
1
Order By: Relevance
“…4) give the values of 9 and 0.04, respectively. The value of r E ϫ r S Ϸ 0.4 reflects the alternating comonomers incorporation being in accord with data by Kakugo et al, 13 Zambelli et al, 31 and Oliva et al 42,43 reported for E/S copolymerization catalyzed with MAO-treated mono-Cp titanium complexes and ansazirconocenes. Contradictory, random comonomer incorporation catalyzed with MAO-treated chelatelike titanium complexes was communicated elsewhere.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…4) give the values of 9 and 0.04, respectively. The value of r E ϫ r S Ϸ 0.4 reflects the alternating comonomers incorporation being in accord with data by Kakugo et al, 13 Zambelli et al, 31 and Oliva et al 42,43 reported for E/S copolymerization catalyzed with MAO-treated mono-Cp titanium complexes and ansazirconocenes. Contradictory, random comonomer incorporation catalyzed with MAO-treated chelatelike titanium complexes was communicated elsewhere.…”
Section: Resultssupporting
confidence: 87%
“…The 13 C-NMR spectra of several E/S copolymers obtained at a different ethylene pressure are presented in Figure 9 (spectra a-c). The sample with the lowest styrene content (ϳ 6 mol %, entry 13) showed 13 C resonance peaks corresponding to isolated styrene units: T ␦␦ (46.6 ppm), S ␣␦ (37.3 ppm), S ␤␦ (28.0 ppm), and S ␦␦ (30.1 ppm) (Fig. 9, spectrum a).…”
Section: Catalytic System In Copolymerization Of E/smentioning
confidence: 97%
See 1 more Smart Citation
“…1 H NMR (300 MHz, C 6 D 6 , 25°C): δ = 7.28 (m, 5 H, CH 2 Ph), 7.11, 7.01 (AAЈ spin system, 2 ϫ 2 H, Ph), 6 [TiPh(η 5 -C 5 H 5 )(η 2 -mbmp)] (6a, 6b, 6c): A 1.8  solution of LiPh in diethyl ether (0.35 mL, 0.62 mmol) was added at -78°C to a solution of 1 (0.30 g, 0.62 mmol) in hexane (50 mL). The reaction mixture was slowly warmed to room temperature and stirred for 12 h. The resulting solution was concentrated under vacuum and a brown oily solid was obtained; spectroscopic analysis revealed a mixture of three isomers 6a, 6b and 6c.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] Recently, several research groups have studied the effect of the cocatalyst on the stereoregularity of propylene polymerization. [17,21,22] We have reported the enhancement of productivity, stereoregularity, and regioregularity as well as increased molecular weight of 1-butene polymerization with a 2,2-thiobis(phenoxy)titanium complex (1) [23][24][25][26] by isobutylmethylaluminoxane (MMAO) modification using water [27] or both water and pentafluorophenol. [28] In these studies, we claim that the addition of water and pentafluorophenol induces the structural and electrical changes in the aluminoxane and the reduction of ''free'' trimethylaluminum (TMA).…”
Section: Introductionmentioning
confidence: 98%